THE ROLE OF INFORMATION TECHNOLOGY IN IMPROVING LOCAL ECONOMIC RESILIENCE - Loso Judijanto; Wahab Wahab (CV. Adiba Aisha Amira, 2024)
In the rapidly growing digital era, Information Technology (IT) has become a crucial component in eflorts to improve local economic resilience. The research method used is literature. The results show that IT is very supportive in improving the operational efficiency of local businesses, expanding market access, and encouraging innovation. E-commerce proves to be an important channel for SMEs to market their products more widely, while the adoption of cloud technology and big data analytics enables smarter and more targeted business decisions. In addition, IT also plays a role in creating a vibrant startup ecosystem, which in turn contributes to job creation and diversification of the local economy. However, the study also identified several challenges in IT implementation, such as the digital divide, the lack of digital skills among the local workforce, and the need for adequate IT infrastructure.